Creating an E-Module on Environmental Pollution Based on Tegal Deso–Okol Local Wisdom: Can It Enhance Students’ Creative Thinking Skills? - Firnanda, Diah Dwi; Asri, Mahanani Tri; Faizah, Ulfi; Rakhmawati, Ismi (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop a valid, practical, and effective learning e-module based on the local wisdom of Gresik (Tegal Deso–Okol) for environmental pollution content to enhance students’ creative thinking skills. The research employed a Research and Development (R&D) method integrating the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with a project-based learning (PjBL) framework. Sixty students from a senior high school in Gresik tested the e-module. Evaluation instruments included validation sheets, student questionnaires, performance rubrics, and learning outcome tests. The validation sheets assessed the feasibility of the e-module, the questionnaires measured practicality, and the performance rubrics evaluated project implementation and presentation. Data were analyzed using descriptive statistics, supported by qualitative feedback to refine the final product. The e-module demonstrated high reliability (92.70) and strong validity (3.77). Its practicality reached 91.67% in Class A and 95.83% in Class B. Students’ creative thinking skills improved substantially, with mean scores increasing from 43.23 to 86.97 in Class A and from 50.47 to 90.01 in Class B. The student response rate (97.5%) and the N-gain score (0.80) also indicate high effectiveness. Overall, integrating cultural values into learning activities through this local-wisdom-based e-module effectively supports the development of students’ creative thinking skills.